Longitudinal Patterns of Suicidality Among Heroin Users in Johannesburg, South Africa: A Need for Suicide Screening and Intervention - Morgan, Nirvana; Denton, Ellen-ge; Subramaney, Ugasvaree; Daniels, William; Steinert, Tilman (Frontiers in Psychiatry, 2022)
Objectives: The objective of the study was to longitudinally assess the outcomes and correlates of suicidal ideation and behavior (SIB) among heroin users who attended inpatient detoxification and psychosocial rehabilitation. SIB was assessed in 300 heroin users upon entry into inpatient detoxification (baseline) as well as 3-months (t1) (n=252; 84%) and 9-months (t2) (n=225; 75%) post treatment. Multivariable logistic regression was used to determine the demographic, clinical and treatment related factors that increased the risk for a high SIB score. Results: From baseline to t1 there was a significant decrease in the proportion of those who endorsed SIB (68.7% vs 38.9%, p<0.0001). There was an increase in the proportion of those who endorsed SIB from t1 to t2 (38,9% vs 47.1%, p=0.047). There was a significant increase in the proportion of those reporting suicide likely in the near future from baseline to t1 (8.7% vs 16.3%: p<0.0049) and this was repeated from t1 to t2 (22.7%) (t1 vs t2: p=0.031). After controlling for all other variables, a comorbid mental illness (MI) at baseline was a significant independent risk factor for a high SIB score at t1(RR 1.63; 95% CL 1.30-2.03) (p<0.0001) and a comorbid MI at t1 increased the risk for a high SIB score at t2 (RR 2.73; 95% CL 1.78-4.19) (p<0.0001)). A poorer general health score and poorer social functioning score at baseline were associated with a high SIB score at baseline (RR 1.02; 95% CL 1.01-1.04) (p=0.001) and t2, respectively (RR 1.07; 95% CL 1.04-1.11) (p<0.0001). Conclusions: Among heroin users, a comorbid mental illness, poorer physical health and poorer social functioning are important factors to consider in suicide risk assessment. Although there were decreases in overall SIB three months after detoxification, this trend was not sustained at 9-month follow-up. After detoxification there were significant increases in the proportion of those reporting a likelihood of suicide in the following three months. The results suggests that the treatment exposure did not adequately mitigate suicide risk. There is a need for review of the treatment as well as targeted screening and management of SIB in heroin users attending treatment services.